ESL foundation learners’ difficulties and strategies applied in writing argumentative essay online / Nur Hani Laily Ramli, Nur Syafiqah Abdul Kadar and Mahfuzah Rafek - Ramli, Nur Hani Laily; Abdul Kadar, Nur Syafiqah; Rafek, Mahfuzah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
Writing is perceived as one the most difficult skills to learn and acquire since learners need to produce a piece of writing where information is systematically in order and easily understood by the readers. Hence, during the process of acquiring the skill in writing, language learners face various difficulties that can cause them to become demotivated and frustrated during writing lessons. Therefore, this study is conducted to determine some of the difficulties faced by ESL foundation learners when they are assigned online writing argumentative essays and strategies applied to overcome the difficulties. This study employed a qualitative method and a semi-structured interview was conducted with 6 second semester ESL foundation learners to identify the difficulties faced by them in online writing argumentative essays. This study also aims to know strategies applied by these learners in order to overcome the difficulties faced by them in online writing argumentative essays. The findings revealed that the majority of the respondents experienced difficulty in generating ideas to write in their online argumentative essay and the majority of them believed that brainstorming activity helps them to overcome the difficulty. Thus, it is important for ESL foundation learners to be exposed to the writing process before they are assigned to essay writing in order to overcome their main difficulty in writing which is to generate ideas for their essay.